Clarifications needed concerning the new Article 59 dealing with pleomorphic fungi - Walter Gams; Hans-Otto Baral; Walter M. Jaklitsch; Roland Kirschner; Marc Stadler (IMA Fungus)
The new rules formulated in Article 59 of the International Code of Nomenclature for algae, fungi, and plants (ICN) will cause numerous, often undesirable, name changes, when only phylogenetically defined clades are named. Our task is to name fungal taxa and not just clades. Two suggestions are made here that may help to alleviate some disadvantages of the new system. (1) Officially an epithet coined in a list-demoted genus that is older than the oldest one available in the list-accepted genus would have to be recombined in the accepted genus. We recommend that individual authors and committees establishing lists of protected names should generally not recombine older epithets from a demoted genus into the accepted genus, when another one from pre-2013 is available in that genus. (2) Because the concepts of correlated teleomorph and anamorph genera are often incongruent, enforced congruence leads to a loss of information. Retaining the most suitable generic name is imperative, even when this is subordinated to another, list-accepted, generic name. Some kind of cryptic dual generic nomenclature is bound to persist. We therefore strongly recommend the retention of binomials in genera where they are most informative. With these recommendations, the upheaval of fungal nomenclature ensuing from the loss of the former Art. 59 can be reduced to an unavoidable minimum.